STUDENTS’ ENGLISH SPEAKING DIFFICULTIES AND TEACHERS’ STRATEGIES IN ENGLISH TEACHING: A CASE STUDY AT MA NURHIDAYAH RABBIN BONTOMANAI - Rahmadani, Wilda; Samtidar, Samtidar; Talib, Ahmad (JTechLP: Journal of Technology in Language Pedagogy, 2023)
The objectives of the research are to identify students with English language proficiency issues and to describe the English teachers’ teaching speaking strategies in dealing based on students’ speaking English difficulties. This research used a qualitative method. This research used previous studies, researchers deliberately choose people and locations to discover or comprehend a key phenomenon. The researcher used a case study research. The researcher used a questionnaire and an interview as two study instruments to gather data from the participants. The subjects of this research are Twelve students, from class X there are 6 students and class XI there are 6 students and there are three English teachers of MA Nurhidayah Bontomanai Sapaya Gowa. The teacher strategies in this research are to use group work, base the activities on sample words, and give some instructions or training in discussion skills. The researcher concluded that students’ difficulties were influenced by two aspects, namely psychological aspects and language aspects. They admitted that they had difficulty speaking English for several reasons because students were worried about making mistakes and felt anxious due to a lack of vocabulary, lack of pronunciation, and lack of topic knowledge, sometimes students wanted to try speaking. Hindered by the lack of vocabulary and messy pronunciation on the other hand because the topics discussed cannot be understood students continue to feel insecure and afraid in trying to speak English in class to appear in front of their class by speaking English and the last students do not have the motivation to fix it.